Pengembangan Sistem Manajemen Aktivitas Berbasis Web dan Mobile untuk Pemilik Rumah Di Desa - Zen Munawar; Novianti Indah Putri; Rita Komalasari; Herru Soerjono; Hernawati; Adang Haryaman (LPPM POLITEKNIK LP3I, 2024)
This research aims to develop a web and mobile system for activity management for homeowners in villages. Villages have a smaller population compared to cities, but as the population in villages increases, activities in villages become more difficult to manage. Developing a web and mobile activity management system is a necessity and needs to be proposed to solve problems in villages. So it is necessary to develop web and mobile system applications so that it makes it easier for village house owners to use cellphones or computers to access village services. Admin can make appointments for village officials and admin can make village reports. Residents who have houses in the village are able to manage family members and guests, edit, update profiles. Apart from that, you can also upload payment receipts for maintenance with this application and can report to the manager if there is a problem around the house. By using this application you can also register animals and vehicles. Guards can monitor guests entering and exiting the village area.. In designing the user interface using Flutter which functions in developing front-end mobile applications and React for websites. On the backend, the Mongo database has been used to connect to both web and mobile platforms.